Management of major bile duct injury after laparoscopic cholecystectomy: a case report. - Manouras, Andreas; Pararas, Nikolaos; Antonakis, Pantelis; Lagoudiannakis, Emannuel E; Papageorgiou, George; Dalianoudis, Ioannis G; Konstadoulakis, Manoussos M (J Med Case Rep, 2009)
INTRODUCTION: Bile duct injury is a severe and potentially life-threatening complication of laparoscopic cholecystectomy. Several series have described a 0.5% to 0.6% incidence of bile duct injury during laparoscopic cholecystectomy. The aim of this study was to analyze the presentation, characteristics, related investigation, and treatment results of major bile duct injuries after laparoscopic cholecystectomy. CASE PRESENTATION: A rare case of a 48-year-old Greek woman with a triple bile duct injury (right and left hepatic duct ligation and common bile duct cross-section) is presented. A Roux en Y hepaticojejunostomy was performed after repeated endoscopic retrograde cholangiopancreatographies, percutaneous transhepatic catheterization of the ducts and magnetic resonance cholangiographies to delineate the biliary anatomy and assess the level of injury. CONCLUSION: Early recognition and an adequate multidisciplinary approach are the cornerstones for the optimal final outcome. Suboptimal management of injuries often leads to more extensive damage to the biliary tree and its vasculature. Early referral to a tertiary care center with experienced hepatobiliary surgeons and skilled interventional radiologists would appear to be necessary to assure optimal results.